Influence of iron on phase stability and corrosion resistance of Ti-15%Cr alloy - Junaidi Syarif; Eko Kurniawan; Zainuddin Sajuri; Mohd Zaidi Omar (Universiti Kebangsaan Malaysia, 2013)
In this study, the effect of Fe addition on the phase stability and corrosion resistance of Ti-15%Cr alloys was investigated. The alloying phenomenon in the specimens was also investigated to determine the effectiveness of the application of pure metallic powders as raw materials for the powder metallurgy method. Ti-15%Cr-1%Fe alloys exhibited needle-like structures within equiaxed structures, while Ti-15%Cr-5%Fe and Ti-15%Cr-10%Fe alloys only showed equiaxed grains. XRD results showed that the β phase could be stabilized by the addition of 5% or more Fe to the alloy. Although the pure powders were used as raw materials, the designated chemical composition, i.e. Ti-15%Cr-(1~10)%Fe can be achieved during sintering. The alloying phenomenon occurred upon sintering due to the high diffusivity of Cr and Fe within the β Ti matrix. The corrosion resistance of the newly developed Ti-15%Cr alloys was significantly improved compared with a commercial Ti-6%Al-4%V alloy.